Providing Warm Compresses for Back Pain in 3rd Trimester Pregnant Women - Nurfaizah, Alvi Sylvia; Choirunissa, Risza; Silawati, Vivi (JOSING: Journal of Nursing and Health, 2023)
This study aims to determine the effect of warm compresses on Low Back Pain in pregnant women in Trimester III at the Bunda Sehat Clinic, Cijantung, Jakarta. The method used in this research is quasi-experimental with pre and post-test design with the control group. The research results show that the average Low Back Pain in Trimester III pregnant women before being given warm compresses was 6.1 (moderate pain), and after being given warm compresses was 2.9 (mild pain). There is an effect of warm compresses on Low Back Pain in pregnant women in the third trimester at the Bunda Sehat Clinic, Cijantung, Jakarta, with a p-value of 0.000. ConclusionkWarm compresses affect reducing Low Back Pain for third-trimester pregnant women at the Bunda Sehat Clinic, Cijantung, Jakarta. Keywords: Pregnancy, Warm Compresses, Low Back Pain